Height and cognitive function among older Europeans: Do people from "tall" countries have superior cognitive abilities? - Cahit Guven; Wang-Sheng Lee (Institute for the Study of Labor (IZA), 2011)
Previous research has found that height is correlated with cognitive functioning at older ages. It therefore makes sense to ask a related question: do people from countries where the average person is relatively tall have superior cognitive abilities on average? Using data from the Survey of Health, Ageing, and Retirement in Europe (SHARE), we find empirical evidence that this is the case, even after controlling for self-reported childhood health, self-reported childhood abilities, parental characteristics and education. We find that people from countries with relatively tall people, such as Denmark and the Netherlands, have on average superior cognitive abilities compared to people from countries with relatively shorter people, such as Italy and Spain. We exploit variations in height trends due to nutritional deprivation in World War II in Europe and use an instrumental variable analysis to further estimate the potential impact of height on cognitive function. We find some suggestive evidence that a causal link from height to cognitive outcomes could be operating via nutrition and not via educational attainment.
urn:nbn:de:101:1-201201107599
Keywords: C21; J24; N3; 330; height; cognitive function; instrumental variables; World War II; Kognition; Biologische Daten; Alte Menschen; Kriegsfolgen; Europa